Power aware switched capacitor integrator design - Korkmaz, Seyrani. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Switched Capacitors are used as resistors because they have better accuracy and they consume less die area than other resistor implementations in integrated circuits. In this technique, a capacitor is charged and discharged in order to transfer charge. This charge transfer is related to switching speed and the value of the capacitance. Transferring charge from one node to other the one with switching gives the ability to control the charge transfer rate in a given time which means controlling the current. Changing the current between two nodes means changing resistance between these two nodes. The value of this capacitance determines the total charge transferred in one switching cycle and how frequently repeating this charging and discharging determines total charge transferred from one node to the other node. Another application of switched capacitor circuits is integrators, transfer ratio between output and input is determined with the ratio of the integrating capacitor over switching capacitor and switching frequency. Switching frequency can be easily controlled and capacitor ratio can also be easily controlled as a multiple of standard capacitors. In this way, switch capacitor integrator can be designed with not too much effort and without trying to adjust input resistor. Designing from switching part to overall switched capacitor integrator, each part will be analyzed in detail to examine which parameters affect on circuits performance. Initially circuit is realized with ideal elements. Then it is realized with the real IC counterparts. Finally switching is analyzed as charge and discharge events to understand which parameters affect the limits of the switching stage and transferred to the second stage. At integrator part, Miller OTA configuration is analyzed to find a solution which will be good enough given input signals, gain, bandwidth and power requirements. During this design phase, power consumption is critical to increase the efficiency of the overall circuit. Because most of the power consumption of the circuit is from opamp or OTA part, thus lowering the power of this part is very important.
Keywords: Capacitors.